2005
DOI: 10.1080/0887044042000272912
|View full text |Cite
|
Sign up to set email alerts
|

Women's expectations and experience of birth

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent repository link: Expectations of birth 2 ABSTRACTThis was an exploratory study with three aims: (1) The results found that anxiety in pregnancy was associated with expecting less positive emotion during birth, more negative emotion during birth, less control and less support during birth. Expectations were positively related to the birth experience. For example, women who expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
65
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 20 publications
8
65
0
7
Order By: Relevance
“…Our results are consistent with the results of the study carried out by Ayers et al 18 . The fi ndings of Stolte study showed that the labor and birth expectations were more different to the actual event in primiparas compared to multiparas 12 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our results are consistent with the results of the study carried out by Ayers et al 18 . The fi ndings of Stolte study showed that the labor and birth expectations were more different to the actual event in primiparas compared to multiparas 12 .…”
Section: Discussionsupporting
confidence: 83%
“…It seems that multiparas would have different expectations due to previous experience of birth as compared to primiparas women. Interestingly, studies have found no signifi cant differences between primiparas and mulitparas in the different variables of expectations except for the variables of body control in labor over staff actions and involvement in decision making 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the light of the Changing Childbirth report (Cumberlege et al, 1993), there has been a growing interest in the last two decades in understanding what women want from maternity services in the United Kingdom (Ayers et al, 2005;Birthrights, 2013;CQC, 2010;Dahlberg and Aune, 2013;Green et al, 2000a;Green et al, 2000b;Redshaw and Heikkila, 2010;Renfrew et al, 2014;Séguin et al, 1989;Walton and Hamilton, 1995). The National Service Framework for Children, Young People and Maternity Services (DH, 2004: 9) purpose is to 'promote high quality, women and child-centred services and personalised care that meets the needs of parents, children and their families', ensuring that childbearing women 'are involved in decisions about what is best for them and have choices about how and where they give birth'.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, no hay consenso en cuanto a su definición (11) . Según Ayers (12) , la expectativa de parto es una construcción compleja y multidimensional que implica muchos aspectos del parto, y en este contexto cabría definirla, en relación al parto, como los "juicios y creencias sobre el futuro que pueden estar influidas por situaciones pasadas" (13) .…”
Section: Introductionunclassified